2017
DOI: 10.1097/ccm.0000000000002463
|View full text |Cite
|
Sign up to set email alerts
|

Two-State Collaborative Study of a Multifaceted Intervention to Decrease Ventilator-Associated Events

Abstract: Objective Ventilator-associated events (VAE) are associated with increased mortality, prolonged mechanical ventilation, and longer ICU stay. Given strong national interest in improving ventilated patient care, the NIH and AHRQ funded a two-state collaborative to reduce VAEs. We describe the collaborative’s impact on VAE rates in 56 ICUs. Design Longitudinal quasi-experimental study. Setting 56 intensive care units (ICUs) at 38 hospitals in Maryland and Pennsylvania from October 2012 to March 2015. Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 34 publications
1
43
0
Order By: Relevance
“…This is similar to data published from 56 ICUs in Maryland and Pennsylvania with 69,417 ventilated patient-days in which compliance with SAT and SBT was 77.5% and 71%, respectively. 24 Our ICUs have a nurse-led sedation vacation protocol and target sedation scores for all sedated patients. Furthermore, we have an SBT protocol that is respiratory therapist driven.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to data published from 56 ICUs in Maryland and Pennsylvania with 69,417 ventilated patient-days in which compliance with SAT and SBT was 77.5% and 71%, respectively. 24 Our ICUs have a nurse-led sedation vacation protocol and target sedation scores for all sedated patients. Furthermore, we have an SBT protocol that is respiratory therapist driven.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Nevertheless, the potential to decrease VAP rates using VAP prevention bundles has been demonstrated by many authors, [17][18][19][20][21][22] and the preventable proportion of VAP was estimated to be 52%-55%. 23,24 Effective implementation is as important as choosing the right bundle components.…”
Section: (Received 8 May 2018; Accepted 22 July 2018)mentioning
confidence: 99%
“…Furthermore, instead of merely being a tool for the surveillance of VAEs, the long-term goal of the VAE algorithm should be to improve outcomes of mechanically ventilated subjects through prevention of VAEs. 5 As shown by Rawat et al, 15 the incidence of VAEs was reduced by 37.6% after implementation of a multifaceted intervention, highlighting the substantial role of the VAE algorithm in improving patient outcomes. Accumulating evidence have shown the crucial need of the conservative fluid strategy in critically ill patients, 27 and we identified in other work the critical role of cumulative fluid balance in critically ill influenza subjects.…”
Section: Discussionmentioning
confidence: 90%
“…A number of studies have characterized the incidence rate of VAE, ranging from 5% to 10% in mechanically ventilated subjects or from 2 to 12 events per 1,000 ventilator days. 2,7,8,10 Rawat et al 15 conducted a longitudinal quasi-experimental study that included 38 hospitals in Maryland and Pennsylvania between 2012 and 2015 and reported that the incidence rate was approximately 5 events per 1,000 ventilator days after the implementation of bundle care consisting of head-of-bed elevation, use of subglottic secretion drainage endotracheal tubes, oral care, chlorhexidine mouth care, and daily spontaneous awakening and breathing trials. In our ICU, bundled care with head-of-bed elevation, oral mouth care using chlorhexidine, daily assessment of sedation status, and spontaneous breathing trials was implemented for all participants and checked daily during the study period, and the incidence of VAE was 7.7 events per 1,000 ventilator days, which is similar to the data reported by Rawat et al 15 (Fig.…”
Section: Discussionmentioning
confidence: 99%